INTENSITAS SERANGAN Spodoptera frugiperda PADA BEBERAPA FASE PERTUMBUHAN TANAMAN JAGUNG - Wilyus Wilyus; Hamdan Maruli Siregar; Rizki Aulia (Jurnal Media Pertanian, 2022)
This study was conducted to determine the attack intensity of S. frugiperda at several stages of corn plant growth. The research was carried out at the Experimental Garden of the Faculty of Agriculture, Jambi University. The research was doneat a 5002 m area of corn plantation which consists of 28 plots with a size of 3 x 2 m for each plot. The variables observed were the intensity of attack of S. frugiperda larvae on the leaves and the percentage of cobs attacked. Observation of attack intensity of S. frugiperda was carried out at all growth phases (phases V3 - V5 to R6 phase), namely by directly observing the symptoms of attack caused by the 3 youngest leaves that were fully opened on each sample plant. Observations of attacked cobs were carried out on all plants in each sample plot starting from the VT - R1 phase to the R6 phase. The results showed that the intensity of the attack of S. frugiperda larvae that attacked the leaves at several stages of corn plant growth fluctuated. The highest attack intensity occurred in the R6 phase, which was 22.92%. Meanwhile, the attack on the cob was first found in the R2 - R5 phase, which was 10% and then experienced a significant increase to 68.57% in the R6 phase.Keywords: attack intensity, maize, S. frugiperda